Justification of Characteristics of Operational-Functional Magnetic Control of Ferroprimes - Sandulyak, A.A.; Sandulyak, A.V.; Ershova, V.A.; Sandulyak, D.A.; Polismakova, M.N. (International Journal of Engineering and Technology, 2018)
The model of operational-functional magnetic control of ferroimpurities is physically substantiated and implemented. In this research the relevant (consistent with the phenomenological) calculation formulas were obtained to determine the total mass of ferroimpurities (including the residual one) in the analyzed sample. In addition to the mass-operational characteristics of magnetic control, the corresponding total accumulative characteristics (including in a generalized form) were obtained and analyzed, confirming validity of the model used.